0.5-V Nano-Power Voltage-Mode First-Order Universal Filter Based on Multiple-Input OTA - Fabian Khateb; Montree Kumngern; Tomasz Kulej (My University, 2023)
This paper presents a new application of the multiple-input operational transconductance amplifier (MI-OTA). The MI-OTA has been used to realize a first-order universal filter which shows that the first-order transfer functions such as low-pass, high-pass, and all-pass filters can be obtained easily from a single topology by applying the input signal to the appropriate terminals. Moreover, both non-inverting and inverting transfer functions of all filtering functions can be obtained. The pole frequency of all filters can also be controlled electronically. The first-order all-pass filters have been selected to realize high-quality band-pass filter. For low-voltage supply operation and extremely low power consumption, the proposed MI-OTA is realized by the multiple-input bulk-driven MOS transistor technique with transistors operating in subthreshold voltage region. The circuit has been simulated using the $0.18 \mu \text{m}$ TSMC CMOS technology with 0.5 V of supply voltage and it consumes 29.77 nW of power for 10 nA nominal setting current. The post-layout simulation results show that the applications of MI-OTA agree well with theory.
Keywords: Operational transconductance amplifier; Transconductance; Subthreshold conduction; Analog and Mixed-Signal Circuit Design